Modeling dependency of crude oil price and agricultural commodity prices: A pairwise copulas approach - Phattanan Boonyanuphong (2018)
This study examines the dependency between the return of crude oil future prices and the agricultural commodity future prices as well as provides flexible models for dependency and the conditional volatility GARCH. Therefore, this paper used copula-based GARCH models, which consists in estimating the marginal distributions of the return of the crude oil price and agricultural commodity prices and then estimates the copula parameters by static and time-varying copula models. The results revealed that the co-movement between crude oil price and agricultural commodity prices are generally strong and there exists symmetric tail dependence between crude oil and agricultural commodity prices in all pairs. However, its tail dependence is relatively weak. The dependence parameters are very volatile over time and deviate from their constant levels. Our findings have important implications for policy makers, producers and traders, which could be used to implement a better policy to optimize and stabilize the markets or their portfolio management in the agricultural commodity markets. © 2013 Springer-Verlag Berlin Heidelberg.